Central and peripheral tumors of multiple myeloma in the Jaws (A case report) - AM Shirani; A Haghighat; SM Razavi (Isfahan University of Medical Sciences, 2007)
Introduction: Multiple myeloma is a malignancy of plasma cells which affect the jaws in 15-30% of the cases. This paper explains a case of the multiple myeloma and its diagnosis.Case Report: The patient was 70 years old; he complained from painful nodule in the mandible interfered in chewing. In clinical examination some nodules were seen in the skull and jaws. In radiographic examination multiple destructive lesions were seen in the skull and jaws. The differential blood count (CBC diff), the urine analyzes, and biopsy was done. The diagnosis was multiple myeloma. More examinations and treatment process were done by oncologist.Discussion: Although this is rare that the first signs of multiple myeloma are in the mouth and a patient comes to the dentist for diagnosis, but knowledge of the signs of this malignancy leads to fast diagnosis and treatment and improving the life time and the quality of life.Key words: Multiple myeloma, Jaws, Peripheral tumors, Central tumors